Between Likeness and Unlikeness: A Fusion of Chinese Ink Painting Aesthetics Into the Medium of Photography - Ping (Heidi), Xu (Auckland University of Technology, 2007)
This is a practice-based research project that explores a new aesthetic perspective and approach in the Western medium of photography, through the application and interpretation of contemporary Chinese master artist Qi Baishi’s philosophical notion of between likeness and unlikeness. Rooted in Chinese ink painting tradition, Qi Baishi [齊白石] (1864-1957) developed and created his theory of achieving likeness in spirit and unlikeness in form as the ultimate goal of painting aesthetics. Adapting Qi’s aesthetics and design approaches to inform the research, and through theoretical explorations and photographic practices, a series of works will be developed that manifests the fusion of Chinese aesthetics with Western photography, to propose a confluent cross-cultural aesthetic thought. The aspiration of drawing upon Qi’s aesthetics at a philosophical level, which is unfamiliar in the context of Western photography, has posed a challenge to the creative exploration. The final outcome is intended to trigger aesthetic resonance in the viewers to further dialectic discussion. The outcome of this research project is presented through a series of photographic works and displayed in a gallery environment.
Keywords: Contemporary; Photography; Aesthetic; Visual; Cross-cultural; Chinese